Evolution of Stars toward the Main Sequence - B. Hidajat (Journal of Mathematical and Fundamental Sciences, 1973)
Abstract. A review on the knowledge of the stellar evolution toward the main sequence is presented. This is the period during which the stars evolve from the beginning of their formation to the phase of stabilization on the main sequence where nuclear reactions begin to provide the entire energy supply. Ringkasan. Dalam tulisan ini diberikan suatu ulasan mengenai evolusi bintang menuju ke deret utama. Yang dimaksud dengan periode evolusi disini ialah periode sejak bintang-bintang tersebut dibentuk, dari materi antar bintang, hingga mencapai saat ketika energi bintang-bintang tersebut dibentuk dengan reaksi nuklir.